Prepared Electrical Resistivity Been Pure B TiO a 3 Impurity - Mohmaed, M. Z.; Rmthan, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
3 BaTiO was prepared by mixing the components of 3 BaCO and 2 TiO by ratio [1:1] ، This paper is devoted to study the effect of radition on the electrical properties of 3 BaTiO . Some of prepared samples were exposed to fast neutrons   SMeV and   MeV14 . In addition ، Some samples were exposed to gamma – ray with dosage   Rad81.5 10  . The results showed that the exposition of some samples to fast neutrons   SMeV and   MeV14 lead to increase the electrical resistivity with the study of the effect of the addition of impurity on electrical resistivity . The addition of two compounds   2 3Yb O and   2 3Sm O lead to decrease of electrical resistivity at a concentration of   0.2 % mol for both compounds ، while the increase of concentration at   0.5 % mol lead to increase electrical resistivity again .